Intra-abdominal hypertension among medical septic patients associated with worsening kidney outcomes (IAH-WK study). Issue 4 (27th January 2023) - Suphatheerawatr, Nitcha; Jaturapisanukul, Solos; Prommool, Surazee; Kurathong, Sathit; Pongsittisak, Wanjak
Abstract : High intra-abdominal pressure (IAP) is associated with acute kidney injury (AKI). However, the relationship between intra-abdominal hypertension (IAH) and AKI in medical septic patients is still inconclusive. This prospective cohort study enrolled patients admitted in the Medical Intensive Care Unit from April 2020 to February 2021. Demographic, therapeutic, and laboratory data were obtained upon admission. The evaluation of IAP was performed via the intra-vesical method during the first and second 24 hours of admission. Kidney function was evaluated on the first 3 days and at least on the 7 th day of enrollment. Among 79 patients, 30 (38%) developed IAH, while 50 (63.3%) developed AKI within 7 days. On the first day, the mean IAP was 15.4 (interquartile range [IQR], 4) and 7.0 (IQR, 3.7) mm Hg in the IAH and non-IAH groups, respectively. A total of 52 patients (65.8%) developed the primary outcome (i.e., a composite outcome including AKI, treatment with kidney replacement therapy, or death). On Cox proportional-hazards model between IAH and outcomes, after adjustment for multiple covariates, IAH was associated with a composite outcome (hazard ratio [HR], 6.5; 95% confidence interval [CI], 2.3–18.6; P < .005) and the development of AKI (HR, 6.5; 95% CI, 2.3–18.8; P < .005). IAH was associated with a composite outcome of AKI, treatment with kidney replacement therapy, or death in medical septic patients. thaiclinicaltrial.org, Identifier: TCTR20200531001, Registered May 24, 2020.